Neonatal oxygen therapy in low- and middle-income countries: a pragmatic review - Jon Zelasko; Moshood O Omotayo; Sara K Berkelhamer; Susan Niermeyer; Lily Kak; Smita Kumar; Pavani K Ram (Journal of Global Health Reports)
# Background